Measurement of the Influences of Social Processes in Appetite using Ecological Momentary Assessment - MacIntyre, Rachel I. (Appetite, 2021)
Obesity and eating disorders are serious health concerns that both involve dysregulated eating patterns, including binge eating and emotional eating. Though social processes and appetite dysregulation have been shown to predict dysregulated eating separately, limited research has examined the potential link between social processes and appetite in daily life. The purpose of the present study was to examine the association between naturally occurring social processes previously linked with dysregulated eating and appetite using ecological momentary assessment (EMA). Thirty women with binge-eating pathology completed five semi-random EMA surveys a day for 14 days. The EMA surveys included measures of social processes that occurred between surveys (i.e., interpersonal problems, body social comparisons, social media use, and external pressures for thinness) and assessments of appetite at time of survey. Multilevel analyses revealed that each social process approximately two-hours prior positively predicted appetite. Further, using lagged analyses, all of the social processes approximately four-hours prior, aside from social media use, predicted appetite. Our findings suggest that social processes are important in predicting appetite among women with binge-eating pathology. Future extensions of this research that include measures of dysregulated eating are needed.